Analysis of the potential of artificial intelligence for professional development and talent management: A systematic literature review - Natalia Tusquellas; Ramon Palau; Raúl Santiago (International Journal of Information Management Data Insights)
The aim of this paper was to analyse the current applications of Artificial Intelligence in professional development and talent management within the corporate world with a focus on corporate training. By means of a Systematic Literature Review based on the PRISMA 2020 reporting criteria this paper highlights the current applications of AI along with the main benefits and drawbacks associated with its implementation. The findings show that AI is being used to enhance recruitment processes, to identify individual training and development skills and needs, to develop personalised training paths, to retain talent and predict attrition, and to detect future workforce skills development needs. It has been outlined that there is a need for automated talent management processes within companies and that talent intelligence should be implemented along with facing the challenges this will entail, such as minimising the risk of bias and hiring high-skilled qualified personnel.